The Influence of Regional Social and Geographic Interaction on the Development of Micro Business Interest in Bakunase II Subdistrict, Kupang City - Saragih, Fernando; Pamungkas, Bella Theo Tomi; Mundiarti, Vanida; Siahaan, Jurdan Martin; Sinlaeloe, Deryl; Taraen, Neki Jekson (Universitas Lambung Mangkurat, 2024)
The research was conducted in the Kupang city area, specifically in the Bakunase II sub-district, because the low number of entrepreneurships can also encourage various economic and social problems, one of which is poverty. Geographical interaction (regional interaction) also has a significant role aimed at knowing the locations taken into account in regional economic studies and the interactions that occur between them influencing the speed of regional development. This research aims to determine whether strong interactions will encourage economic development and business development as well as economic equality in each region in the city of Kupang using Nearest Neighbor Analysis. The method used in this research is descriptive quantitative method. The results of this research are that the geographic interaction distribution pattern has a positive and significant effect on interest in entrepreneurship with the percentage of micro businesses amounting to 54 units or 96.43%, small businesses amounting to 2 units or 3.57% and medium businesses amounting to 0 by looking at the most dominant distribution of goods. comes from Oebobo District with a percentage of 39.29%. distribution of Micro, Small and Medium Enterprises (MSMEs), Population Distribution Map, and Goods Distribution Map.